2007
DOI: 10.4269/ajtmh.2007.76.909
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Visceral Leishmaniasis and Asymptomatic Leishmanial Infection in a Highly Endemic Bangladeshi Village

Abstract: We examined the epidemiology of kala-azar and asymptomatic leishmanial infection measured by serologic and leishmanin skin test results in a Bangladeshi community. In a subset, we measured serum retinol, zinc and C-reactive protein (CRP). Kala-azar and seroconversion incidence were 15.6 and 63.1 per 1,000 person-years, respectively. Proximity to a previous kala-azar case increased the likelihood of both kala-azar and asymptomatic infection. Bed net use protected against kala-azar (rate ratio = 0.35, P < 0.01),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
132
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(156 citation statements)
references
References 43 publications
(59 reference statements)
14
132
1
1
Order By: Relevance
“…However, we believe that serologic results were still likely to be reliable because reversion to negative serologic results is slow in treated VL patients, taking more than a year in most cases. 30 Unfortunately, our study was conducted at a time when routine HIV testing was not available at the field site. Subsequent routine HIV testing demonstrated that 18% of adult VL patients treated at the AZHC in 2007 had co-infection with HIV; the prevalence in the general population was estimated to be 2.1%.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that serologic results were still likely to be reliable because reversion to negative serologic results is slow in treated VL patients, taking more than a year in most cases. 30 Unfortunately, our study was conducted at a time when routine HIV testing was not available at the field site. Subsequent routine HIV testing demonstrated that 18% of adult VL patients treated at the AZHC in 2007 had co-infection with HIV; the prevalence in the general population was estimated to be 2.1%.…”
Section: Discussionmentioning
confidence: 99%
“…HIV co-infections), patients with concomitant conditions (e.g. severe malnutrition) (Alvar et al, 2008;Cerf et al, 1987;Anstead et al, 2001;Dye and Williams, 1993;Bern et al, 2007), and those with limited treatment access due to conflict, famine or population displacement (Reithinger et al, 2007). Even amongst patients with access to VL treatment, the estimated case-fatality rate is 10% (Alvar et al, 2012).…”
Section: Geographical Distribution and Disease Burdenmentioning
confidence: 99%
“…to underestimate R 0 ), as there are sections of the host-vectorparasite population combinations that are transmitting at a much higher rate than the rest. For Leishmania in particular, there is sufficient field evidence to suggest that rates of transmission and disease vary significantly through both time (Dye and Wolpert, 1988) and space (Bern et al, 2007;Woolhouse et al, 1997), and between individuals (Courtenay et al, 2014) so that there is unlikely to be a good "average" situation. But without sufficient data to understand the important spatio-temporal scales, the correct scale of appropriate spatio-temporal studies is unknown; for example, is annual assessment of a village sufficient, or should studies be based on monthly assessment of households in at least five villages?…”
Section: Current Data and Initial Modelsmentioning
confidence: 99%
“…As cattle are the preferred host for P. argentipes, the sand fly vector of VL in the Indian subcontinent, cattle may act as reservoir of VL. Although there are reports of VL in Bangladesh (Bern et al, 2007) but the epidemiology of VL and the possible role of cattle for VL transmission has not been studied in Bangladesh so far.…”
Section: Introductionmentioning
confidence: 99%